Metastasis of Colorectal Adenocarcinoma to the Thyroid: A Case Report and Review of the Literature - C. Goatman; P. J. Goldsmith; V. Antonopoulos; B. Ali (Case Reports in Surgery)
Purpose. We present a rare case of colorectal metastasis to the thyroid five years following primary colonic resection. This case highlights the need to be cognisant of unusual sites of metastasis from colorectal neoplasms. Case Report. An 82-year-old male patient had a panproctocolectomy for synchronous colorectal tumours. Five years later he was found to have lung and thyroid metastases found incidentally on imaging for an acute presentation with small bowel obstruction. Conclusion. Metastases to the thyroid should be considered in the differential diagnosis of the thyroid lesion with any history of malignancy, particularly with increasing patient age and when renal cell carcinoma or lung, colon, or breast primaries are involved.